Viability characterization of a proof-of-concept Bluetooth mesh smart building application. (May 2022) - Eras, Leonardo; Domínguez, Federico; Martinez, Caril
Bluetooth low energy is an almost ubiquitous technology currently embedded in billions of power-constrained Internet of Things devices around the world. The Bluetooth mesh profile, released by the Bluetooth Special Interest Group in July 2017, allows Bluetooth low energy devices to form a mesh network, further enabling smart home and building applications where long-range connectivity is required. However, the current release of Bluetooth mesh profile still has power and deployment constraints that limit its applicability. To explore the viability of Bluetooth mesh profile in home/building automation applications, we built the Smart Doorbell: a proof-of-concept Bluetooth mesh profile–based visitor notification system for office spaces. The Smart Doorbell was implemented using a mesh network topology with nodes distributed across office building floors, serving as a real Internet of Things deployment and as a testbed for mesh network protocols. Similar Bluetooth mesh profile evaluations found in literature use mostly development kits and/or synthetic traffic in artificial settings; we contribute by using the Smart Doorbell, a system as close as possible to a minimum viable product, to evaluate power consumption and responsiveness as a proxy for product viability. This article presents the architecture of the Smart Doorbell, the viability evaluation results, and a direct comparison with FruityMesh, a competing Bluetooth low energy mesh network protocol. Overall, the fact that Bluetooth mesh profile devices can directly communicate with a user's mobile phone (using Bluetooth low energy) considerably eases deployment and provisioning. However, the use of flooding to forward messages across the mesh network increases power consumption, precluding the use of battery-powered nodes on the network's backbone and severely limiting the applicability of Bluetooth mesh profile in building automation.